Fast high-resolution lifetime image reconstruction for positron lifetime tomography - Bangyan Huang; Zipai Wang; Xinjie Zeng; Amir H. Goldan; Jinyi Qi (Communications Physics)
Abstract Due to the ortho-positronium formed prior to the annihilation, the lifetime of a positron is sensitive to the tissue microenvironment and can potentially provide valuable information for monitoring disease progression and treatment response. However, the lifetime of positrons before annihilation has long been overlooked in current positron emission tomography (PET). Here we develop a positron lifetime image reconstruction method called SIMPLE (Statistical IMage reconstruction of Positron Lifetime via time-wEighting) and demonstrate its performance using a real scan on a time-of-flight PET scanner. The SIMPLE method achieves high-resolution positron lifetime imaging of extended heterogeneous tissue illuminated by a 22Na point source, successfully resolving the boundary between muscle and fat. It delivers spatial resolution comparable to that of conventional PET activity images while maintaining a computational cost equivalent to reconstructing two PET images. This work paves the way for clinical translation of high-resolution positron lifetime imaging.